Nilotinib-Induced Immune-Mediated Liver Injury: Corticosteroid as a Possible Therapeutic Option - Yang, Hyun; Sung, Pil Soo; Jung, Eun Sun; Cho, Sungwoo; Bae, Si Hyun; Kim, Dong-Wook (Frontiers in Oncology, 2020)
Introduction: Nilotinib is a BCR-ABL tyrosine kinase inhibitor approved for chronic myeloid leukemia. We present a case of severe immune-mediated liver injury by nilotinib treatment. Case report: A 59-year-old woman was referred to the liver clinic because of elevated liver enzyme levels. One year prior, she was diagnosed as having chronic myeloid leukemia and treated with nilotinib therapy. The level of aspartate aminotransferase and alanine aminotransferase were 578 IU/L and 499 IU/L, respectively. Percutaneous needle liver biopsy showed extensive centrilobular infiltration of immune cells and destruction of the lobular architecture with minimal inflammation in the portal triad. Immunohistochemical staining showed that many CD8+ T cells and CD56+ cells infiltrated the site of inflammation. Multicolor fluorescence-activated cell-sorting analysis revealed that a considerable number of intrahepatic CD8+ T cells showed an activated phenotype compared with the healthy control. She was diagnosed with nilotinib-induced, immune-mediated liver injury. Prednisolone treatment (30 mg daily) was started and caused rapid normalization of liver enzyme levels. Conclusion: Nilotinib can cause immune-mediated liver injury. The use of corticosteroid can be treatment option in immune-mediated liver injury.